Advances in the application of information technology to sport performance - Liebermann, D. G.; Katz, L.; Hughes, M. D.; Bartlett, R. M.; McClements, J.; Franks, I. M. (Journal of Sports Sciences, 2002)
This paper overviews the diverse information technologies that are used to provide athletes with relevant feedback. Examples taken from various sports are used to illustrate selected applications of technology-based feedback. Several feedback systems are discussed, including vision, audition and proprioception. Each technology described here is based on the assumption that feedback would eventually enhance skill acquisition and sport performance and, as such, its usefulness to athletes and coaches in training is critically evaluated.